BENİGN PARATESTİKÜLER TÜMÖRLER: OLGU SUNUMU - AKKUŞ, Emre; ÖZALP, Ali Uğur; ÇAKALIR, Canser (Cerrahpaşa Medical Journal, 2014)
Background.- Paratesticular tumors are rarely seen and originate from paratesticular tissues of the testes. They can also be called as fibrous pseudotumors of the testis. They may also be defined as the benign fibrous proliferation of the tunica vaginalis of the testis. We present the diagnostic and therapeutic approach of a case of benign paratesticular tumor. Observation.- Here we report a 30 years old man who had admitted to our clinic with a painless scrotal mass. His history revealed no trauma or previous scrotal disorder. The ultrasonographic evaluation revealed multipl hypoechogenic vascular mass lesions which protruded into the scrotal cavity. Painless small extratesticular lesions were palpated in the hemiscrotum during the physical examination. The laboratory results of Beta HCG, Alfafetoprotein and LDH were within normal values. Scrotal exploration was performed under general anesthesia. Tunica vaginalis oriented smooth surfaced peduculated masses were excised and pathological evaluation of the frozen section revealed benign. The patient was discharged from the hospital next day without any complication. Further pathological evaluation revealed myofibroblast proliferation, inflammatory infiltration and of hyalinized areas with no malignancy.